Sınıf Öğretmenlerinin Derslerinde Kullandıkları Yöntem ve Tekniklere İlişkin Görüşleri: Bir Olgubilim Araştırması - Karasu Avci, Emine; Ketenoğlu Kayabaşi, Esra (Hacettepe University Journal of Education, 2018)
The inclusion of methods and techniques in the learning-teaching process makes it necessary for teachers to identify methods and techniques. The purpose of this study is to determine what the methods and techniques used by classroom teachers in their lessons are. This study is a qualitative research. The study group of the study is composed of 30 class teachers working in Agri, Antalya, Gaziantep, Kastamonu, Konya, Sakarya, Sanliurfa, Sirnak and Yozgat in the spring semester of 2016-2017 academic year and accepting voluntarily to participate in the study. Research data was obtained by applying correspondence technique. The obtained data were analyzed by descriptive analysis. In the direction of the aim of the study, the subjects of the methods and techniques used by classroom teachers in Turkish, Mathematics, Life Science, Social Sciences and Science and Technology lessons and the issues that they pay attention while using these methods and techniques have been determined. The teachers of the class stated that they mostly use methods and techniques in Science and Technology and Life Science courses. Classroom teachers frequently use lectures, question-answer, drama and debate in Turkish lessons; Expression, question-answer and problem solving in mathematics lesson; Expression, question-answer and role playing in Life Science lesson; Lecture, question-answer and drama in social studies course; In science and technology class, they used experiment, question-answer and narration. They have associated the reasons for using these methods and techniques with the level of the students and their relevance to their interests and needs. Class teachers see themselves as sufficient in the general sense of using methods and techniques.
Keywords: Classroom teacher; method and technique; lesson; Sınıf öğretmeni; yöntem ve teknik; ders; 4. Education; 10. No inequality; 16. Peace & justice